Aparat biurokratyczny orzecznictwa karno-administracyjnego Polski Ludowej - Łysko, Marcin (Komunizm: System - Ludzie - Dokumentacja, 2013)
In April 1952 in Poland there was introduced a collegiate settlements of minor offence proceedings by social factors. The legal and organizational attendance of the jury was given to criminal-administrative departments of national council bureaus. The personnel of those departments was too limited in comparison to the needs and included mainly people with no professional qualifications. Low wages efficiently discouraged employees to take jobs in the criminal-administrative system. Personnel problems were reflected in the low level of criminal-administrative jurisdiction in the 1950s. After the crucial for after-war Poland year 1956 the Ministry of Internal Affairs, which was supervising the juries, tried to improve the criminal-administrative system. However, facing lack of support from the central government it was not capable of solving the problem of personnel liquidity and an inadequate number of lawyers in the system attending the juries. It was not until the second half of the 1960s when some bills were passed, which made improving the system by employing people with legal qualifications possible. However, the personnel was still not numerous enough to cope with the range of tasks, which had a negative impact on the level of juries for minor offences functioning.